Energy Consumption and Economic Growth Nexus: New Empirical Evidence from Nigeria - Abalaba, Bamidele Pereowei; Dada, Matthew Abiodun (International Journal of Energy Economics and Policy, 2013)
This study analysed the trend of energy consumption, real output, financial development, monetary policy rate and consumer prices and also examined the long-run relationship and direction of causality between energy consumption and economic growth with consideration for financial development, monetary policy rate and consumer prices. These were with a view to examining the relationship between energy consumption and economic growth in Nigeria during the period 1971-2010. The result showed that all the variables used in the study are characterized by a positive trend. Also, it was found that variables followed a I(1) process. The study provides weak evidence in support of long-run relationship between energy consumption and economic growth. The study further revealed that energy consumption among other variables positively and significantly influenced output growth in the short-run. Using the first three lags, we found no causal evidence one way or two way between energy consumption and economic growth. The study concluded that energy consumption only has short-run positive impact on the economy but has not enhanced long-run economic growth in Nigeria during the period under investigation. Keywords: Error correction model; aggregated analysis; energy consumption; financial development; monetary policy rate JEL Classifications: O13; O47; Q43